Diffusion of Organic Agriculture Communication Innovations as an Effort to Mitigate Climate Change - Muhamad Hidayat; Dedy Irwandy; Achmad Hamudi Assegaf (Ikatan Sarjana Komunikasi Indonesia, 2025)
The long-standing use of synthetic fertilizers and pesticides has created habits and dependency among farmers. Inorganic materials have become commonplace and it seems as if there are no other options to use as farming inputs. Basically, synthetic-based agricultural production materials can damage the environment and potentially harm farmers. Most farmers in the Subak Wengaya Betan Farmers Group have switched from using inorganic materials to organic ones up to now. This should serve as an example of how farmers in Subak Wengaya Betan can adopt organic farming innovations. This research aims to analyze the diffusion process of organic agricultural communication innovations as an effort to mitigate climate change in the Subak Wengaya Betan Farmers Group, Bali Province. The main process in qualitative research was chosen to obtain in-depth results through the data collection stage using interviews, observations, and other documentation to gather detailed information as data collection techniques. The results of this study indicate that effective steps that can be accepted by farmers to transition to organic farming include the development of a social system closely tied to local wisdom, along with the active participation of customary or village officials who possess and earn the trust of the community. Keywords: Diffusion of innovation; communication; mitigation; organic farming; climate change